2014
DOI: 10.1016/j.jes.2014.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty analyses on the calculation of water environmental capacity by an innovative holistic method and its application to the Dongjiang River

Abstract: The estimation and allocation of water environmental capacity (WEC) are essential to water quality management and social-economic interests. However, there is inevitable uncertainty in the capacity estimation due to model conceptualization, data collection and parameter calibration. An innovative holistic approach was developed, which took both independence and relevance between parameters into account to analyze the uncertainties in WEC calculation and estimate the margin of safety. The Dongjiang River was ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…A simple mathematical model has low requirements for data and high-calculation speed but low calculation accuracy (Yan et al 2019). The complex mechanism model has high-calculation accuracy, but the data are difficult to obtain, and the calculation efficiency is low (Chen et al 2014). Simple mathematical models include one-dimensional models and two-dimensional models (Zhou et al 2017).…”
Section: The General Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple mathematical model has low requirements for data and high-calculation speed but low calculation accuracy (Yan et al 2019). The complex mechanism model has high-calculation accuracy, but the data are difficult to obtain, and the calculation efficiency is low (Chen et al 2014). Simple mathematical models include one-dimensional models and two-dimensional models (Zhou et al 2017).…”
Section: The General Frameworkmentioning
confidence: 99%
“…Wang et al (2019) calculated the daily WEC by using the Soil and Water Assessment Tool (SWAT) model, and the results showed that the WEC was positively correlated with rainfall intensity and that nonpoint source pollution had a great impact on the WEC. However, the random uncertainty of factors such as flow and background concentration that were used to calculate the WEC leads to the random uncertainty of the WEC (Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to flow rate, another key parameter for WEC estimation is the integrated degradation coefficient (k), which determines the decay rate of the contaminant in the river channel. In previous studies based on steady-state model, k was usually considered to be a constant [ 3 , 12 , 25 ]. Actually, it has been confirmed that k is simultaneously affected by flow velocity and water temperature [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the acceleration of economic development and urbanization, China's water environment problems have become more and more serious (Zhou et al, 2017). Research and calculation of water environment carrying capacity is one of the foundations of water environment management (Liu et al, 2012a;Chen et al, 2014;Wang et al, 2015). The specific concept of water environment carrying capacity has not yet reached consensus in academia and the understanding of water environment carrying capacity is mainly divided into two types currently.…”
Section: Introductionmentioning
confidence: 99%